The Effect Of Career Competencies On Job Satisfaction Through Perceived Employability And Work Engagement - Prameswari, Riyantyari Hayu; Sridadi, Ahmad Rizki (Universitas Muhammadiyah Jember, 2019)
The current labor market requires workers to have high career competencies. WHO (2013) further states that in the health sector, in an effort to realize progress in the field of human resource health, competent and trained health workers are one of the keys to achieving job satisfaction and universal health coverage as a whole. Kong et al. (2013) states that workers with high career competencies tend to show positive traits that lead to high job satisfaction. An interesting phenomenon is that although in general the competency of health workers in Surabaya's Husada Utama Hospital is relatively high, but it still leaves the problem of salary dissatisfaction, especially in the nursing division. This phenomenon underlies the interest of researchers to examine more deeply the influence of career competencies on job satisfaction. In addition, in terms of theory, the influence of career competencies on job satisfaction, especially in the health care industry is still rarely examined in Indonesia, moreover by involving the variable perceived employability and work engagement as a mediating variable. This study aims to determine the effect of Career Competencies on Job Satisfaction through Perceived Employability and Work Engagement. This research is a quantitative study, in which the study sample is 160 permanent nurses at the Husada Utama Hospital in Surabaya. The method used in data analysis is SEM. The results of data analysis support each research hypothesis, where career competencies have a positive and significant effect on perceived employability, work engagement, and job satisfaction. In addition, it was also concluded that perceived employability and work engagement each partially mediated the influence of career competencies on job satisfaction